Risk factors and seroprevalence of hepatitis E evaluated in frozen‐serum samples (2002‐2003) of pregnant women compared with female blood donors in a Southern region of Brazil. Issue 12 (3rd September 2018) - Hardtke, S.; Rocco, R.; Ogata, J.; Braga, S.; Barbosa, M.; Wranke, A.; Doi, E.; da Cunha, D.; Maluf, E.; Wedemeyer, H.; Muzzillo, D.
Abstract : Hepatitis E has always been related to morbidity in pregnant women. Its epidemiology is not well understood in Brazil. Therefore, we tested sera from 209 pregnant women and 199 female blood donors, collected at a single center in Curitiba, Brazil. The Wantai assay was used for testing the anti‐hepatitis E virus (anti‐HEV), immunoglobulin G (IgG), and an in‐house polymerase chain reaction process for testing HEV RNA. Anti‐HEV was detected in 22.5% of the total group, 19% in the pregnant women group, and 26% in the blood donor group ( P  = 0.11), a much higher prevalence when compared with other studies in Brazil. Demographical analysis showed that 92.4% were born in the South Region of Brazil, 4.9% in the Southeast, and 2.7% were distributed over other regions of the country. With respect to their origin, 99% were from the South, 0.7% from the Southeast, and 0.2% from the Central‐West regions. Income, education, race, number of pregnancies, and abortion did differ significantly when comparing both the groups ( P  < 0.001). Age >30 ( P  = 0.012) and the number (>3) of pregnancies ( P  = 0.008) were related to anti‐HEV positivity. All anti‐HEV IgG–positive females were HEV RNA negative. In conclusion, HEV positivity was found in one out of five young women, which showed an urgent need for further epidemiological studies in Brazil.